MEREDEFINISI KAMPUNG: PARADIGMA BARU PERENCANAAN KOTA DALAM MEWUJUDKAN KOTA YANG LEBIH BAIK - Maria Iqnasia Karen; Dewi Ratnaningrum; Maria Veronica Gandha (Jurusan Arsitektur dan Perencanaan, 2021)
The rapid growth of the urban population on limited land pushes the city to grow vertically. Vertical development is clearly very helpful in overcoming the problem of high density, yet the existing module for vertical existence has produced an urban landscape of formal and monotonous that pushes the population to become socially disconnected. This paper aims to propose a new typology of a vertical dwelling in densely populated settlements in Urban Kampoong through a strategy of redevelopment, based on the form of community interaction and characteristics of urban village known as Kampung, in Tambora, West Jakarta. At some point, urban village has presented a new concept of urban development which is compact city, in terms of density, land efficiency with mixed land use pattern, and complex-dynamic social systems, that ensure the sustainability of the kampung and creates a livable community. Furthermore, within the framework of the